2008
DOI: 10.1007/s10103-008-0614-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of receptor activator of nuclear factor -κB ligand, receptor activator of nuclear factor -κB, and osteoprotegerin, following low-level laser treatment on deproteinized bovine bone graft in rats

Abstract: The aim of this study was to investigate by immunohistochemistry the effects of low-level laser (LLL) irradiation on the expression of the receptor activator of nuclear factor -kappaB ligand (RANKL), osteoprotegerin (OPG), and the receptor activator of nuclear factor -kappaB (RANK) in deproteinized bovine bone grafts in rats. Twenty-four male Sprague-Dawley rats aged 15 weeks were allocated to either an experimental group that underwent LLL irradiation during bone healing at the bone graft sites of the rats' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…[11][12][13][14] Some research studies have examined how low-intensity lasers affect the mechanism of bone regeneration, but there is much controversy, which indicates the need for more research to obtain certainty about how LILT afffects bone tissue. [15][16][17][18][19][20] However, in vitro and in vivo studies have showed a significant stimulation of the irradiation on the bone/implant complex, which is related to the ability of laser irradiation to accelerate cellular activity, such as improved alkaline phosphatase (ALP) activity synthesis, 21 early osteoblastic differentiation, 22 and release of growth factors. 23 The ALP is regarded as a marker of osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Some research studies have examined how low-intensity lasers affect the mechanism of bone regeneration, but there is much controversy, which indicates the need for more research to obtain certainty about how LILT afffects bone tissue. [15][16][17][18][19][20] However, in vitro and in vivo studies have showed a significant stimulation of the irradiation on the bone/implant complex, which is related to the ability of laser irradiation to accelerate cellular activity, such as improved alkaline phosphatase (ALP) activity synthesis, 21 early osteoblastic differentiation, 22 and release of growth factors. 23 The ALP is regarded as a marker of osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. (42) reported that LELI facilitated bone metabolism during bone healing in rats. Further, Hamajima et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental and clinical studies describe that PBMT aids in the process of tissue regeneration, demonstrating biological modulatory effects on cell differentiation [9,16,17]. Photobiomodulation of bone tissue seems to increase the results of fracture repair [18], periodontal tissue [19], implant osseointegration [20] and bone reconstruction with or without biomaterials [15,[21][22][23][24][25]. Its application in clinical practice with the purpose of assisting healing after bone graft reconstruction surgery [26] is still poorly described in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…The literature cites as necessary in the reconstruction of bone defects three simultaneous conditions: (i) osteoconductive properties; (ii) inductive properties; and (iii) the presence of bone-forming cells [35]. As an alternative material, bovine bone graft [15,20,[36][37][38][39] is the most widely used due to its biocompatibility characteristics, as indicated in reconstructive areas related to traumatology, cranio-maxillary surgery, facial prosthetic rehabilitation, skeletal aging and esthetic aging [28]. Physical methods, such as low-intensity ultrasound (LIPUS) [40] and photobiomodulation therapy (PBMT), have the potential to improve the bone reconstruction process, acting or not in combination with bone grafts.…”
Section: Introductionmentioning
confidence: 99%